LAS CARTAS DE CABARRÚS (1808) Y LA TRADICIÓN REGLAMENTARISTA EUROPEA EN MATERIA DE PROSTITUCIÓN - Jiménez Salcedo, Juan (Anales de Filología Francesa, 2008)
In this article Cabarrús’ Cartas (1808) are compared with other reglamentarist texts on prostitution in 18th century Europe, especially Rétif de la Bretonne’s Le Pornographe (1770). This article also provides a general insight on prostitution in France and Spain during the second half of the 18th century.